2018
DOI: 10.1111/1750-3841.14164
|View full text |Cite
|
Sign up to set email alerts
|

Using Cellulose Nanofibers and Its Palm Oil Pickering Emulsion as Fat Substitutes in Emulsified Sausage

Abstract: Cellulose nanofibers present a variety of distinguishing properties, such as large surface area, great stability and high strength. The ability to stabilize emulsions and good biocompatibility enlarge its application in food. In this study, we attempted to use cellulose nanofibers and its palm oil Pickering emulsion as fat substitutes to partly replace the original fat of pork emulsified sausages, hoping to provide some basic information for using cellulose nanofibers and its Pickering emulsion as fat substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 51 publications
(73 reference statements)
5
35
0
Order By: Relevance
“…It could be seen that the dried orange by-products contain high level of crud fiber and low level of fats. our results are in agreement with those reported by(Wang et. al., 2018) who found that orange waste contains 4.7% moisture, 7.39% ash, 1.85% fat, 7.0% pectin.…”
supporting
confidence: 94%
See 1 more Smart Citation
“…It could be seen that the dried orange by-products contain high level of crud fiber and low level of fats. our results are in agreement with those reported by(Wang et. al., 2018) who found that orange waste contains 4.7% moisture, 7.39% ash, 1.85% fat, 7.0% pectin.…”
supporting
confidence: 94%
“…Strategies to reduce the fat content in meat products are based on using lean meat cuts that can increase cost and/or replacing the fat with dietary fiber plus water, bringing a functional appeal and reducing the impact on sensory properties (Wang et al, 2018).…”
Section: Effect Of Orange By-product As Fat Replacer On Quality Propementioning
confidence: 99%
“…The pH value of heated pork batters decreased approximately 0.15 units from 5.98 to 5.83, due to the addition of BSDF. However, previous researches found that incorporating some dietary fibers, such as cellulose nanofibers and hydrated wheat fiber, did not affect the pH of meat batter systems [29,30]. The decrease in pH was probably associated with the acidic components in BSDF.…”
Section: Resultsmentioning
confidence: 85%
“…In recent years, to cater to the increasing health concept of consumers, many scientists have considered adding vegetable oils to the minced batter to replace the fat. The addition of nano‐cellulose and palm oil as fat substitutes in emulsion sausage was found to result in lower cooking loss and higher moisture content (Wang et al., 2018). Cheetangdee (2017) reported that emulsified SPI with fish protein isolate partially substitute for pork back fat could improve the quality of emulsified sausages.…”
Section: Introductionmentioning
confidence: 99%